Effects of cyclic loading directions on liquefaction characteristics of saturated coral sand - LIU Kang; CHEN Guo-xing; WU Qi; MA Wei-jia; QIN You (Rock and Soil Mechanics, 2021)
The large scale construction of both military and civil infrastructures located in Nansha reefs and offshore marine areas, South China Sea, has raised the seismic safety a challenging issue for the projects in the region. The influences of fines content (FC) on the liquefaction characteristics of saturated terrestrial quartz sands have been extensively studied, but the corresponding research on saturated coral sands in reclaimed coral islands is less involved. Using the GDS hollow cylinder torsion shear apparatus, a series of isotropically consolidated undrained cyclic tests have been performed on saturated coral sand sampled from the Nansha Islands, South China Sea. The samples are prescribed with the stress path formed under the 90° jump rotation of principal stress with various cyclic loading directions. The influences of the inclination angle (αd) of the major principal stress and fines content FC on the liquefaction characteristics of saturated coral sand are investigated. It has been discovered that, regarding the zero effective stress state as initial liquefaction criterion, the liquefaction resistance of saturated coral sand decreases with the increase of αd for 0°≤αd≤45° and FC for 0%≤FC≤30%. The correlation among the generalized shear strain amplitude (γga), the fines content FC, and the revolution of residual excess pore water pressure of saturated coral soil has been clearified. By introducing a unit cyclic stress ratio USR as a new index for liquefaction resistance and based on binary medium theory, the expression between the unit cyclic stress ratio USR15, inducing initial liquefaction in 15 cycles, and the equivalent skeleton void ratio e*sk for the saturated sands is established for the test. The theory is validated by the experimental data in the literature.